Income Distribution among Women through Local Wisdom in Indigenous Communities (Saemaul Undong Spirit Approach) - Hahury, Hendri Dony; Oppier, Hermi; Pattimahu, Terezia V (MAKILA, 2025)
This study examines communities' efforts to address income distribution inequality by leveraging local wisdom mechanisms. Income inequality is observed at regional and national levels and manifests in gender disparities. This research aims to explore how local wisdom, particularly the practice of "picking nutmeg seeds," serves as a mechanism for mitigating income inequality experienced by women. This study seeks to understand women's income distribution behaviors through the lens of local wisdom. Data collection methods include in-depth interviews, participant observation, and focus group discussions (FGDs), while data analysis is conducted using thematic analysis to identify, analyze, and report emerging patterns. The findings reveal that the traditional practice of nutmeg collection functions as an informal insurance mechanism, ensuring the sustainability of household livelihoods, particularly for widowed women in the Negeri Booi-Samahu Amalatu Indigenous community. Furthermore, the research highlights the role of local institutions within the nutmeg farming community in fostering a system of shared prosperity rather than shared poverty. This collective well-being is achieved without the exploitation of community members, including women, particularly widows. Additionally, according to the Saemaul Undong principle, local wisdom strongly correlates with rural development and community empowerment. Through active participation, resource management, and self-reliance, local wisdom is a foundation for sustainable community development and equitable economic opportunities.